2016
DOI: 10.1038/cddis.2016.217
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase inhibition aggravates kidney injury in the absence of CD2AP

Abstract: Inappropriate activation of the Wnt/β-catenin pathway has been indicated in podocyte dysfunction and injury, and shown to contribute to the development and progression of nephropathy. Tankyrases, multifunctional poly(ADP-ribose) polymerase (PARP) superfamily members with features of both signaling and cytoskeletal proteins, antagonize Wnt/β-catenin signaling. We found that tankyrases interact with CD2-associated protein (CD2AP), a protein essential for kidney ultrafiltration as CD2AP-knockout (CD2AP−/−) mice d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…Both TNKS1 and TNKS2 are expressed in WAT in db/db and db/+ mice ( Fig. S4A), migrating at 160 kDa and 130 kDa, respectively, as previously demonstrated by transient overexpression in HEK293 cells [20]. G007-LK reduced the protein level of TNKS1 and TNKS2 in WAT in both genotypes ( Fig.…”
Section: G007-lk Induces Axin1 Accumulation In Wat and Muscle In Db/dsupporting
confidence: 82%
See 1 more Smart Citation
“…Both TNKS1 and TNKS2 are expressed in WAT in db/db and db/+ mice ( Fig. S4A), migrating at 160 kDa and 130 kDa, respectively, as previously demonstrated by transient overexpression in HEK293 cells [20]. G007-LK reduced the protein level of TNKS1 and TNKS2 in WAT in both genotypes ( Fig.…”
Section: G007-lk Induces Axin1 Accumulation In Wat and Muscle In Db/dsupporting
confidence: 82%
“…TNKS-mediated PARylation depends on the sequence of the TNKS-binding motif and the structural features of the binding partner [ 19 ]. Consequently, not all binding partners become PARylated [ 19 ], and some even inhibit the PARylation activity of TNKSs [ 20 ]. In humans, TNKS (the gene encoding tankyrase 1, TNKS1) localizes to chromosome 8p23.1, a susceptibility locus for T2DM [ 21 ], and variants of TNKS associate with early-onset obesity [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In CD2AP−/− podocytes, SHIP2 inhibition did reduce ROS but aggravated apoptosis. Resembling this, we observed previously increased activity of β-catenin in podocytes in the absence of CD2AP, but found that inhibition of the Wnt/β-catenin pathway did not ameliorate but further aggravated kidney injury 41 . These data reinforce the central role of CD2AP as a regulator of multiple pathways in podocytes and reveal that inhibition of the harmful pathways may have unexpected adverse effects.…”
Section: Discussionmentioning
confidence: 70%
“…Podocyte damage results in numerous glomerular diseases, including nephritic syndrome and nephrotic syndrome ( 87 ). Kuusela et al ( 30 ) demonstrated that tankyrases interact with CD2AP, and CD2AP is a negative tankyrase regulator. Tankyrase inhibition in the absence of CD2AP increases kidney damage, which indicates that tankyrases are essential for maintaining normal kidney function ( 87 ).…”
Section: Novel Tankyrase Binding Partnersmentioning
confidence: 99%